Skillful performance in Tennis Game and its relationship to Morale among students of Sports Institutes - Mohammed, Chachan Juma; Abdullah, Musab Mohammed (Journal of Educational and Psychological Sciences, 2021)
The present study aimed to identify the level of skill performance in the game of Tennis and Moral among students of government sports institutes in the Kurdistan region of Iraq, and the significance of the differences according to the variables: (governorate, age, and institute). The sample of the study consisted of (169) students who were intentionally chosen from among the students. The study used the descriptive approach in the correlative and comparative method. (SPSS) used by both researchers in dealing with the data of research. The results showed that the level of skill performance in the game of tennis among students of sports institutes is low, and no significant differences in Skill performance attributed to demographic variables. The Moral level of the study sample found high. The results showed that there was no significant difference in Moral due to the variables of age and governorate; the result indicated significant differences in Moral according to institutes. The results also indicated that there was no statistically significant relationship between skill performance and Moral. In light of the results, a set of recommendations and proposals has presented.